Multiscreening LC-MS/MS Designed for Ten Pesticide and Six Antimicrobial Residues in Eggs - Julia Arantes Galvão; Ricardo Seiti Yamatogi; Alexander Welker Biondo; José Paes de Almeida Nogueira Pinto; José Roberto Marques Silva; Caio Antonio Carbonari; Edivaldo Domingues Velini (Journal of Food Quality)
A multiscreening method was experimentally validated for pesticide and antimicrobial residues in spiked eggs at levels of 5, 50, and 500 μg L−1. The residue extraction was performed with acetonitrile and 1% formic acid. The extracted material was stored at −70°C until detection and quantitation within 24-hour period by LC-MS/MS. Pesticide and antimicrobial residue recovery performed adequate standard deviation and the results were from 94.10% (ampa) to 9.20% (carbaryl) for pesticides and from 95.70% (enrofloxacin) to 46.20% (sulfathiazole) for antimicrobial. The method was highly accurate, considering the linearity for all pesticide and antimicrobial residues (r2>0.99), with quantitation limits ranging from 0.78 to 6.25 μg L−1 for pesticides and 0.78 to 3.13 μg L−1 for antibiotics. A highly correlation coefficient (r>0.99) was found, except for carbaryl. Although time extraction and carbaryl recovery remain to be improved, the method has shown a rapid pesticide and antimicrobial residue detection.